Types and Functions of Interjections in Wole Soyinkas Ala?pata? A?pa?ta and Yoruba Speech Community - Samuel Adebayo Omotunde; Samuel Oyeyemi Agbeleoba (Journal of Language and Literature, 2019)
Interjections are universal means of communication among human beings which pass across different emotions and information in different cultures and languages. However, while some are found in nearly all languages but with varied meanings and functions according to context, some are peculiar to specific languages and cultures. This work, therefore, investigates the functions and meanings of both universal interjections (specifically Oh and Ah) and the Yoruba language specific interjections found in Wole Soyinkas Ala?pata? A?pa?ta. The work also discusses two other significant Yoruba language specific interjections although they are not found in the analyzed text. The authors chose the text because it is replete with interjections Oh and Ah which carry various meanings and perform various functions (few of which have not been discussed in the literature) and also because it contains the Yoruba language specific interjections which probably have not been investigated in the literature, thereby contributing to knowledge.Keywords: universal interjections, Yoruba language specific interjections, Ala?pata?